2019
DOI: 10.1002/lary.28237
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography performance in predicting extranodal extension in HPV‐positive oropharynx cancer

Abstract: Objectives: To evaluate the performance characteristics of seven predetermined imaging features on pretreatment computed tomography (CT) in identifying extranodal extension (ENE) in cervical lymph node metastases from human papillomavirus-positive oropharyngeal carcinoma (HPV-OPC).Study Design: Retrospective study. Methods: Seventy-three patients with HPV-OPC who underwent primary surgery and cervical lymph node dissection were included. Preoperative contrast-enhanced CT (cCT) imaging was evaluated by two radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 40 publications
(57 reference statements)
2
46
0
Order By: Relevance
“…The area under the receiver operating characteristics curve for diagnosing ENE and lymph node metastases was 0.91 (95% CI = 0.85-0.97)-ENE of lymph node metastases could be predicted with a sensitivity of 88% and specificity of 85% (22). The diagnosis of ENE by means of CT was additionally the subject of the recently published work by Faraji et al (15). Seventy-three patients with HPV-positive OPSCC treated by primary surgery and neck dissection were reviewed for the presence of seven defined criteria of CT imaging (15).…”
Section: Imaging and Clinical Predictors In Diagnosing Extranodal Extmentioning
confidence: 98%
See 3 more Smart Citations
“…The area under the receiver operating characteristics curve for diagnosing ENE and lymph node metastases was 0.91 (95% CI = 0.85-0.97)-ENE of lymph node metastases could be predicted with a sensitivity of 88% and specificity of 85% (22). The diagnosis of ENE by means of CT was additionally the subject of the recently published work by Faraji et al (15). Seventy-three patients with HPV-positive OPSCC treated by primary surgery and neck dissection were reviewed for the presence of seven defined criteria of CT imaging (15).…”
Section: Imaging and Clinical Predictors In Diagnosing Extranodal Extmentioning
confidence: 98%
“…The diagnosis of ENE by means of CT was additionally the subject of the recently published work by Faraji et al (15). Seventy-three patients with HPV-positive OPSCC treated by primary surgery and neck dissection were reviewed for the presence of seven defined criteria of CT imaging (15). The pretreatment CT scans were evaluated by two radiologists who were blinded to the pathologic ENE results (15).…”
Section: Imaging and Clinical Predictors In Diagnosing Extranodal Extmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 Another potentially useful lymph node feature is nodal matting, which is defined as three or more lymph nodes abutting together with the absence of intervening fat planes. 11,12 It can be evaluated by sonography, computed tomography (CT), or magnetic resonance imaging (MRI), [11][12][13][14] and has been shown to be an important prognostic factor for some cancers. 11,[15][16][17] Sivridis et al 15 found that nodal matting and nodal necrosis were associated with poor prognosis, independent of N-stage in node-positive breast carcinomas.…”
mentioning
confidence: 99%